The Audit and Review of Service Performance Information in the New Zealand Charity Sector - Filimoehala, Kainga-he-lotu (Auckland University of Technology, 2021)
The purpose of this research study is to explore the current practices of the audit and review of service performance information in the charity sector. Performance audit is an accountability mechanism that has been used in the public sector as a way to exercise accountability while assessing the “economy, efficiency and effectiveness” of public sector performance (Parker, Jacobs, & Schmitz, 2019, p. 285). In response to accountability issues and reporting quality, the New Zealand charity sector have introduced performance audit into charity reporting, and interestingly enough it has been regulated amongst the small to medium sized charities. As of 1 January 2021, a new statutory audit regulation for the audit of service performance information was made effective: the NZ AS 1: New Zealand Auditing Standards 1. This standard has been created solely as a specific statutory audit regulation for service performance information. However, since the introduction of Service Performance reporting in April 2015, charities have been required to either audit or review their performance report. Despite the recent introduction of the NZ AS 1, there have already been existing standards which cater towards the audit or review of non-financial information. This study investigated into the current practices of audit and review of service performance information using the current standards that have been used for the past few years. Based on 400 performance reports collected from a sample of 200 Tier 3 charities, this study conducted a qualitative research which aimed at building an understanding into the current practices of the audit of service performance information in the charity sector. This study finds that the performance audit of the public sector differs from the performance audit that is currently practiced in the charity sector in terms of focus, terminology and practice. It is seen that while audit is the analysis of the true and fair view of financial information, when it comes to the non-financial information, specifically, the Service performance information, the audit and review is a conclusion on its suitability and practicability. What suitability means is based on the judgement of the assurance provider and how they confirm the relevance, completeness, neutrality, reliability and understandability of a charity’s disclosed outputs and outcomes for the year. The findings also show that the conceptualisation of these characteristics is confusing amongst its practice. This study contributes to current literature as it finds that the policing role of charity regulators is seen to take place in the allocation of new standards and while it is a good thing it has also identified that there is the need to strengthen the educating role of charity regulators as there seems to be a misunderstanding in the conceptualisation of the qualitative characteristics. The findings of this study is useful for accounting standard setters, accounting professional bodies and assurance practitioners.
Keywords: Service Performance information; Performance audit; Charity regulation; Outputs and outcomes; Charity audit